Struktur Pendapatan, Tingkat Kesejahteraan Dan Faktor Produksi Agroforestri Kopi Pada Kesatuan Pengelolaan Hutan Lindung Batutegi (Studi Di Gabungan Kelompok Tani Karya Tani Mandiri) - Sri Winarni; Slamet Budi Yuwono; Susni Herwanti (Jurnal Sylva Lestari, 2016)
Community forestry program is an effort to save the forests while providing benefits to society. Society was given license to manage forests laden not develop plant species monoculture systems but with agroforestry systems. Canopy multi strata agroforestry systems of benefits economical and ecological that matter to farmers, one of which can provide income for farmers. So that the implementation of agroforestry systems community forestry land is expected to be a solution the needs of land as a factor of production as well as to the recovery of the forest is mainly a function of the life support system. The goal of the research determined the structure of income, the factors that influence of income and welfare level of coffee agroforestry as participants community forestry program. To analyze factors affecting farmers' income analyzed by linear regression of multiple and welfare of farmers based price of rice by Sajogyo 1997. From the reckoning, income of farmers amounted of coffee agroforestry to Rp 14,649,631/KK/Year and Rp 6,321,690/KK/year of activity non agroforestry dominated farming and as much as 38,10% of farmers prosperous based on income from the activity coffee agroforestry at community forestry. The results regression analysis variables influential real against earnings agroforestry is the land area and the dependents of family. Keywords: income, income factors, welfare level